A Rectangular Dielectric Resonator Antenna with a Wideband Circular Polarization excited by an H-Shaped Conformal Metal Strip - Illahi, U.; Iqbal, J.; I. Sulaiman, M.; Alam, M.; S. Mazliham, M. (International Journal of Engineering and Technology, 2018)
A unique conformal H-shaped metal strip has been used to excite a rectangular dielectric resonator antenna (DRA). By using this proposed single feeding technique, a broadband circular polarization has been produced. A circular polarization bandwidth of ~17.6% and an impedance-matching bandwidth of ~21.6% with a useful overlap of ~14.4% has been achieved. The Computer simulation technology (CST), a 3D simulation tool has been used to design and simulate the antenna prototype. The design has been successfully built and simulated using Finite Integration Technique (FIT). The results of FIT has been validated by Finite Element Method (FEM) i.e. another simulation technique available in CST. A great resemblance between the results from FIT and FEM has been observed.Â Â